The Pathologic Diaphragm. (15th May 2017) - Daugherty, Michael; Kucera, Jennifer Neville; Harvey, Maria
Abstract : A brief review of diaphragmatic anatomy and functionality is necessary before the discussion of the various pathologic diaphragmatic entities. The diaphragm begins developing during the first trimester and is composed of four primary structures, including the transverse septum (which ultimately becomes the central tendon); pleuroperitoneal folds, esophageal mesentery; and the muscular body wall.1 Three separate normal diaphragmatic openings or "hiatuses" are present, which allow for communication between the thoracic and abdominal cavities (Figure 1 ). The inferior vena cava (IVC) hiatus is located in the midportion of the central tendon and contains the IVC and right phrenic nerve branches. The aortic hiatus is retrocrural in position and contains the aorta, thoracic duct, azygos vein, and hemiazygos vein. The esophageal hiatus is located in the right diaphragmatic crus and contains the esophagus, sympathetic branches, and the vagus nerve. Considered the weakest of the three, the esophageal hiatus is the most common site for visceral herniation.2 Motor and sensory innervation of the diaphragm is provided by the bilateral phrenic nerves, which is formed from the C3-C5 nerve roots.3 As the diaphragm contracts, intrathoracic pressure decreases, which pulls air into the lungs with help from the secondary respiration muscles. Relaxation of the diaphragm then allows for exhalation as air exits the thoracic cavity. In addition to serving as the primary muscle of ventilation, the diaphragm also assists with regulation of intra-abdominal pressure encountered in several processes including urination, emesis, and defecation.1 In normal individuals, the right diaphragm is higher than the left, and the anterior and medial segments of the diaphragm are higher than the posterior and lateral segments.3 Disruption of normal diaphragmatic embryologic development and physiology leads to various pathologic entities that the radiologist should be able to recognize. Pathology reviewed in this article includes congenital and acquired hernias, diaphragmatic eventration, and diaphragmatic paralysis.